Knowledge And Awareness About Anatomic Root Form Implants Among Undergraduate Dental Students- A Survey - P, Kalyani; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Anatomic root form implants or the root analogue implants are implants which can be placed immediately after extraction. The characteristic feature of these implants is that they mimic the natural root anatomy and can be placed into the extraction socket immediately after extraction. Further, there aren’t much bone augmentation procedures involved. The Anatomic root form implants are made of Zirconia, which is one of the most biocompatible materials ever used in dentistry Aim: The aim of this study is to determine the level of awareness about Anatomic root form implants among undergraduate dental students. Materials and methods: This is a questionnaire-based survey. The questionnaire consisted of questions with multiple responses for each question. The questions were framed based on the following: Disadvantages of conventional implants, advantages of root form implants, design of root form implants, the process of making root form implants, etc. The participants were undergraduate students (IV years and interns) of a city based dental college. Results: Around 40% of the respondents felt that the major disadvantage of conventional implant is that it being expensive and also its incongruous anatomy. 35% responded that the natural Anatomy was the main advantage of Anatomic root form implants. Conclusion: The respondents in this study were quite aware about some facts concerned with Anatomic root form implants. However, a clear idea about the process and placement of such implants needs to be created among the undergraduate students.